Safety and Efficacy of Tenecteplase in Older Patients With Large Vessel Occlusion: A Pooled Analysis of the EXTEND-IA TNK Trials. (22nd March 2022) - Yogendrakumar, Vignan; Churilov, Leonid; Mitchell, Peter J.; Kleinig, Timothy J.; Yassi, Nawaf; Thijs, Vincent; Wu, Teddy Y.; Shah, Darshan G.; Ng, Felix C.; Dewey, Helen M.; Wijeratne, Tissa; Yan, Bernard; et al.
Abstract : Background and Objectives: Detailed study of tenecteplase (TNK) in patients older than 80 years is limited. The objective of our study was to assess the safety and efficacy of TNK at 0.25 and 0.40 mg/kg doses in patients older than 80 years with large vessel occlusion. Methods: We performed a pooled analysis of the EXTEND-IA TNK randomized controlled trials (n = 502). Patients were adults presenting with ischemic stroke due to occlusion of the intracranial internal carotid, middle cerebral, or basilar artery presenting within 4.5 hours of symptom onset. We compared the treatment effect of TNK 0.25 mg/kg, TNK 0.40 mg/kg, and alteplase 0.90 mg/kg, stratifying for patient age (>80 years). Outcomes evaluated include 90-day modified Rankin Scale (mRS) score, all-cause mortality, and symptomatic ICH. Treatment effect was adjusted for baseline NIH Stroke Score, age, and time from symptom onset to puncture via mixed effects proportional odds and logistic regression models. Results: In patients >80 years (n = 137), TNK 0.25 mg/kg was associated with improved 90-day mRS (median 3 vs 4, adjusted common odds ratio (acOR) 2.70, 95% CI 1.23–5.94) and reduced mortality (acOR 0.34, 95% CI 0.13–0.91) vs 0.40 mg/kg. TNK 0.25 mg/kg was associated with improved 90-day mRS (median 3 vs 4, acOR 2.28, 95% CI 1.03–5.05) vs alteplase. No difference in 90-day mRS or mortality was detected between alteplase and TNK 0.40 mg/kg. Symptomatic ICH was observed in 4 patients treated with TNK 0.40 mg/kg, 1 patient treated with alteplase, and 0 patients treated with TNK 0.25 mg/kg. In patients ⩽80 years, no differences in 90-day mRS, mortality, or symptomatic ICH were observed among TNK 0.25 mg/kg, alteplase, and TNK 0.40 mg/kg. Discussion: TNK 0.25 mg/kg was associated with improved 90-day mRS and lower mortality in patients older than 80 years. No differences among the doses were observed in younger patients. Trial Registration Information: NCT02388061, NCT03340493. Classification of Evidence: This study provides Class II evidence that tenecteplase 0.25 mg/kg given before endovascular therapy in patients >80 years old with large vessel occlusion stroke is associated with better functional outcomes at 90 days and reduced mortality when compared to tenecteplase 0.40 mg/kg or alteplase 0.90 mg/kg.